Obstacles to rural development in Hit and ways to address them - Al-Duleimi, Ammna Jabbar Muttar Daewish; Obaid, Shahlaa Ayad (Al-Adab Journal, 2021)
The research tackles the most important obstacles that impede the achievement of rural development in the study area, the most important of which are related to natural resources and represent (constraints on the climate, nature of the surface, pollution of the soil, water resources, the problem of salinity, desertification and erosion), as well as constraints on resources Humanity (high population growth rate, ownership and agricultural holdings, use of technology and technical requirements, traditional adherence to agricultural heritage, reduction of government credit, abandonment of agricultural work for security reasons, potable water services, electricity services, problem Health, educational and recreational services, urban sprawl, agricultural prices, and the disadvantages of marketing), and then discussed the most important future solutions through the development of development plans to promote the reality of rural development and the estimates that must be taken into consideration in the future when formulating development plans.